Geochemical composition of Tanzanian shelf sediments indicates Holocene climatic and sea-level changes. Issue 3 (5th April 2017) - Liu, Xiting; Rendle-Bühring, Rebecca; Henrich, Rüdiger
Abstract: We present a high-resolution geochemical and grain-size record from a Holocene sediment core off the Pangani River mouth, Tanzania. Elemental ratios between biogenic elements and Al (i.e., Ca/Al, Mg/Al, and Sr/Al) are mainly influenced by terrigenous dilution on carbonate concentration and/or limitation of carbonate production as a result of variations in the supply of fine-grained terrigenous sediments of the Pangani River. Such elemental ratios increased significantly at the end of the mid-Holocene between 5 and 3.5 ka, demonstrating a gradual transition from the humid early and mid-Holocene to the arid late Holocene in East Africa. Among the elemental ratios between terrigenous elements and Al, Si/Al and K/Al ratios correlate to grain-size variation, indicating a change in sedimentation regime. Fe/Al and Ti/Al ratios show that the sediment source area has shifted from the terrestrial volcanic region of Tanzania (Fe, Ti rich) to the coastal and inner-shelf regions (Fe, Ti poor) around 7.5 ka, in response to arid climate and high sea level. Our geochemical results correspond with a sea-surface temperature record derived from the same sediment core, indicating that the end of the East African Humid Period could have been gradual and related to the cooling water in the western Indian Ocean.